Формування сучасної кримськотатарської літератури - Латышева, Е.В. (Культура народов Причерноморья, 2006)
У статті розглядається формування сучасної кримськотатарської літератури в Україні. В статье рассматривается формирование современной крымскотатарской литературы в Украине. The problem of revival and formation of modern Crimean Tartar literature during the establishment of the Independence of Ukraine is examined in this article.